2006
DOI: 10.1080/14697680500168008
|View full text |Cite
|
Sign up to set email alerts
|

Large stock price changes: volume or liquidity?

Abstract: We analyze large stock price changes of more than five standard deviations for i) TAQ data for the year 1997 and ii) order book data from the Island ECN for the year 2002. We argue that large price changes are not due to large trading volumes. Instead, we find that extreme price fluctuations are mainly caused by a low density of limit orders stored in the order book, i.e. a small liquidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 31 publications
5
56
2
6
Order By: Relevance
“…Hypothesis (3) is that this is due to selective liquidity taking, i.e. that liquidity takers submit large orders when liquidity is high and small orders when it is low (see ), Weber and Rosenow [2006], and Hopman [2006]). …”
Section: Why Is Individual Transaction Impact Concave?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothesis (3) is that this is due to selective liquidity taking, i.e. that liquidity takers submit large orders when liquidity is high and small orders when it is low (see ), Weber and Rosenow [2006], and Hopman [2006]). …”
Section: Why Is Individual Transaction Impact Concave?mentioning
confidence: 99%
“…This is defined as the average price change that would instantaneously occur for an effective market order of size v (Weber and Rosenow [2006]), Farmer and Zamani [2007]). In Figure 6 we show the virtual impact for AZN, computed by hypothetically submitting orders for a range of different values of v and measuring the immediate price response.…”
Section: Why Is Individual Transaction Impact Concave?mentioning
confidence: 99%
“…It is found that the virtual price impact is much stronger than the actual impact [4] and large price fluctuations are not necessarily caused by large orders but rather the liquidity [5,6]. It is rational that a large trader prefers to split his large order and submit when the opposite LOB is thick such that the price does not change much.…”
Section: Introductionmentioning
confidence: 99%
“…Arriving limit orders significantly reduce the impact of trades [44] and the concave shape of the price impact function changes depending on the contemporaneous limit order arrivals [41]. The outstanding limit orders (also known as market depth) significantly affect the impact of an individual trade ( [30]) and low depth is associated with large price changes [45,17]. Hasbrouck and Seppi [22] use depth as one of the factors that determine price impact.…”
Section: Introductionmentioning
confidence: 99%